Are Kenya's horticultural exports a replicable success story? - Minot, Nicholas; Ngigi, Margaret (International Food Policy Research Institute, 2004)
The authors describe the case study as follows: "Kenyan horticultural exports have grown at over 6 percent per year for the past 30 years. Since 1974 the value of Kenya's horticultural exports has increased fourfold in constant dollar terms, reaching US$167 million in 2000 (see figure). As a result, horticulture has become the third largest source of foreign exchange after tourism and tea. More than 25,000 small farmers participate in the sector, accounting for over half of Kenyan horticultural exports." They then examine the impacts and the driving forces of the Kenyan experience and conclude with the key lessons for future successes.